2020
DOI: 10.3390/cli8010009
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Economic Impact of Climate Change on Crop Production in the Dry Zone of Myanmar: A Ricardian Approach

Abstract: Myanmar is the country with the highest economic vulnerability (EV) to climate change in the Southeast Asian region. The dry zone of Myanmar occupies two-thirds of the agricultural lands and it has higher temperatures than elsewhere in the country. Climate change has severe impacts on agricultural production in this region. Moreover, changes in the precipitation patterns increase the likelihood of crop failures in the short-run and production declines in the long run. Therefore, an assessment of the economic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…From the literature, the potential influence of climate variability on crop production is mainly sensitive to rainfall and other inter-variable dependence such as temperature and evapotranspiration variabilities [49][50][51]. This is because crop production needs optimal precipitation and tolerable temperature ranges for growth and development [52], and drought variations may potentially reduce crop production and affect the agricultural systems of countries with no climate literacy or weak implementation strategy [50].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the literature, the potential influence of climate variability on crop production is mainly sensitive to rainfall and other inter-variable dependence such as temperature and evapotranspiration variabilities [49][50][51]. This is because crop production needs optimal precipitation and tolerable temperature ranges for growth and development [52], and drought variations may potentially reduce crop production and affect the agricultural systems of countries with no climate literacy or weak implementation strategy [50].…”
Section: Introductionmentioning
confidence: 99%
“…Myanmar is one of the most vulnerable countries in the region due to her diverse agro-climatic conditions [49]. Past studies showed that Myanmar has experienced both precipitation and temperature changes over the last decade [53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also argue that the evidence on global greening and the response of agricultural crops to enhanced CO2 availability suggests that the productivity boost is likely stronger than that parameterized in FUND. Oo et al (2020) measure the economic impact of climate change on crop production in Myanmar, through a Ricardian approach. A cross-sectional survey covering three regions in the central dry zone: (Magwe, Mandalay, and Sagaing regions) was conducted, yielding a sample of 425 farmers.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%
“…A griculture and food production is strongly influenced by adverse weather and climate change, especially if experienced during critical stages of growth. It influences food production directly through changes in agro-ecological conditions and indirectly by affecting the growth and the distribution of incomes, and thus the demand for agricultural production (Schmidhuber and Tubiello 2007;Tun Oo et al 2020;Boer and Surmaini 2002). Climate change is likely to contribute substantially to food insecurity in the future, due to increasing food prices, and reducing food production.…”
Section: Introductionmentioning
confidence: 99%